Effects of increasing dietary lysine in phase ii diets (15- to 25-lb) on nursery pig growth performance - Usry, J.L.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 1,260 weanling pigs (initially 18.6 lb) was used in a 19 d growth assay (d 10 to 29 after weaning) to determine the effects of increasing lysine in Phase II diets on nursery pig growth performance. All pigs were weaned and fed 1.2 lb per pig of a SEW diet, then switched to a transition diet until day 10 after weaning. Pigs were then weighed and switched to experimental diets containing true digestible lysine levels of 1.22, 1.32, 1.42, 1.52, and 1.62%, corresponding to approximately 1.36, 1.47, 1.56, 1.65, and 1.75% total lysine. All diets were formulated to contain 30% soybean meal, with increasing amounts of synthetic amino acids to achieve desired amino acid concentrations in the diets. From d 10 to 17 after weaning, increasing lysine increased ADG (quadratic, P<0.04) and improved feed efficiency (quadratic, P<0.01), with both appearing to be maximized at 1.52% true ileal digestible lysine. From d 17 to 24 and 24 to 29, ADFI and F/G improved (linear, P<0.05) with increasing true ileal digestible lysine. For the overall study, (d 10 to 29 after weaning), increasing true ileal digestible lysine increased ADG (quadratic, P<0.07) and improved feed efficiency (quadratic, P<0.001). In conclusion, 1.52% true ileal digestible lysine maximized both ADG and F/G early in the study, but the lysine requirement appeared to decrease to 1.42% from d 17 to 24. Results of two recent studies conducted at the University of Missouri with similar lysine levels fed to 15- to 25-lb pigs suggest a requirement estimate between 1.32 and 1.42% true ileal digestible lysine, slightly lower than the requirements observed in the present study.
Keywords: Nursery pig; Phase II; Lysine requirement; Growth; Swine